폐탄광지역 비소오염 농경지(논) 개량 시 복토두께에 따른 비소의 벼 전이 및 토양용액 특성 - 고일하; 권요셉; 정문호; 고주인; 박관인; 지원현; Koh, Il-Ha; Kwon, Yo Seb; Jeong, Mun-Ho; Ko, Ju In; Bak, Gwan-In; Ji, Won Hyun (자원환경지질, 2021)
This study was carried out to investigate the feasibility of reducing clean cover soil using a flooded column test in arsenic-contaminated farmland reclamation of abandoned coal mine area that shows generally low or about worrisome level (25 mg/kg) of Korea soil environment conservation act unlike abandoned metal mine. During the monitoring period of soil solution for 4 months, chemical properties (pH, EC, ORP, Fe, Mn, Ca, and As) in each layer (clean soil cover and contaminated/stabilized soil) showed different variation. This result revealed that soil solution in stabilized or contaminated soil rarely affected that in cover soil. Whether stabilized or not, arsenic concentrations in the rice roots grown in the soil covers with the thickness of 40 cm decreased by 98% in compared with the that grown in the control soil. In case of the soil covers with 20 cm thickness on stabilized soil, it decreased by 80% and this was 22 percentage point higher than when the soil of lower layer was not stabilized. Thus, reducing clean cover soil could be possible in contaminated farmland soil reclamation if appropriate stabilization of contaminated soil is carried. 본 연구에서는 폐금속광산과는 달리 우려기준 전후의 낮은 비소 오염농도 분포특성을 가지는 폐석탄광산 농경지 토양을 대상으로 광해방지사업(토양개량·복원사업) 시 복토층의 두께 감소 가능여부를 벼를 식재한 담수형 컬럼실험을 통해 검토하였다. 담수 후 4개월 동안 토양용액의 pH, EC, ORP 및 무기원소(Fe, Mn, Ca, As) 농도를 모니터링한 결과 컬럼하층에서 상층으로 미치는 영향은 높지 않은 것으로 나타났다. 복토 두께에 따른 비교에서도 하층의 영향보다는 복토층 두께 변화에 따른 ORP 변화가 복토재 무기원소의 거동에 영향을 미치는 결과를 보였다. 이러한 결과는 토양용액의 거동이 상하층간 반응의 영향보다는 각 층별 나타나는 토양의 이질성에 우선하여 나타난 것으로 판단되었다. 모니터링 종료시점에서 채취한 벼 뿌리의 비소 농도는 현행 사업 조건과 같은 40 cm 두께의 복토층을 조성한 경우 컬럼하층의 안정화 처리여부에 상관없이 대조구 대비 98%가 감소되었다. 20 cm 두께의 복토층에서는 오염토의 안정화가 없을 경우 58%, 안정화처리 시 80%의 전이감소 효율을 나타내었다. 따라서 오염 농경지 토양에 대한 적정 안정화 처리를 수행할 경우 복토재의 사용량을 감소시킬 수 있으며, 경제적인 사업수행효과도 이룰 수 있을 것으로 판단된다.